PP.17.05: THE EFFECTS OF TISSUE EXSANGUINATION AND TISSUE ENGORGEMENT ON BLOOD PRESSURE AND ITS MEASUREMENT. (June 2015) - Naveed, U.; Pollard, C.; Lewis, P.
Abstract : Objective: Accurate measurement of systolic blood pressure (SBP) is important in assessing cardiovascular disease. Oscillometric BP machines are increasingly replacing auscultatory methods and are affected by arm composition and BMI. The objective is to evaluate the accuracy of oscillometric blood pressure (BP) measurement in tissue exsanguination and tissue engorgement and the effect of repeated BP measurement on local tissues. Design and method: Sixty-two subjects (F: 41, M: 21) aged 18 to 71 were studied. SBP was measured in triplicate using an oscillometric BP machine and radial Doppler return to flow. Triceps skinfold thickness (TST) and arm circumference (AC) were also measured in each of three situations: normal arm, after exsanguination with Rhys-Davies exsanguinator and engorgement using an upper arm cuff inflated to 30 mmHg for five minutes. Results: Means of oscillometric SBP readings of 108.84 mmHg (normal), 107.48 mmHg (exsanguinated) and 107.71 mmHg (engorged) are similar (p = 0.177). In all of the three situations the TST (p = 0.000) increased and AC (p = 0.000) decreased. Oscillometric SBP was similar in both arms at normal but exsanguination (p = 0.004) and engorgement (p = 0.003) of the non-dominant arm caused an increase in SBP measurement in the contralateral side. Conclusions: Measurement of SBP by oscillometric BP machines is questionable as repeat measurements on the upper arm cause the SBP to level, AC to reduce and TST to increase, independent of the physiological state. These local tissue changes (AC and TST) interfere with oscillometric measurement of SBP. Tissue manipulation by exsanguination and engorgement causes changes to SBP centrally (observed rise in SBP on contralateral side).